2020
DOI: 10.1186/s12886-020-01745-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological biomarkers of the vitreous responsible for proliferative alteration in the different forms of retinal detachment

Abstract: Background The purpose of the study was to explore the immunological components that are responsible for the proliferative alterations in the different forms of retinal detachment (RD). Methods Vitreous fluids were collected during 23G pars plana vitrectomy from 54 eyes of 54 patients with different RD types, such as rhegmatogenous RD (RRD) without proliferative vitreoretinopathy (PVR) (n = 30), PVR (n = 16) and proliferative diabetic retinopathy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…IL-8 is produced by phagocytes and mesenchymal cells and activates, recruits, and promotes extravasation and the respiratory burst of neutrophils. Several studies suggest that chemoattraction and neutrophils are involved in the retinal detachment and PVR disease processes [ 20 , 22 ]. Furthermore, Takahashi et al hypothesized that IL-8 levels could reflect the level of photoreceptor damage given that IL-8 was found to be positively correlated with the extent of detachment, and photoreceptor cell damage indirectly increases IL-8 expression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-8 is produced by phagocytes and mesenchymal cells and activates, recruits, and promotes extravasation and the respiratory burst of neutrophils. Several studies suggest that chemoattraction and neutrophils are involved in the retinal detachment and PVR disease processes [ 20 , 22 ]. Furthermore, Takahashi et al hypothesized that IL-8 levels could reflect the level of photoreceptor damage given that IL-8 was found to be positively correlated with the extent of detachment, and photoreceptor cell damage indirectly increases IL-8 expression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MIP-1β promotes the migration and adhesion of macrophages and microglia [ 58 , 59 ]. Additionally, IP-10 is a pro-inflammatory chemoattractant for monocytes and macrophages and functions as an anti-angiogenic and antifibrotic agent ( Table A2 ) [ 20 , 21 , 22 ]. Therefore, while IP-10 may attract leukocytes to the inflamed area of retinal detachment, it may also counteract the fibrotic actions of MCP-1 and MIP-1β as proposed by Takahashi et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study applying proteomic analysis of preretinal PVR membranes identified ECM organization and extracellular structure organization as two pathways that were enriched in PVR [61]. Another study analyzing vitreous cytokines, chemokines, and growth factors in eyes undergoing vitrectomies identified elevated levels of CTACK, IP-10, SCGF-beta, and SDF-1 alpha in patients with PVR and diabetic tractional RDs [62 ▪ ]. A study identified Myo/Nog cells, which are involved in fibrosis, for the first time in preretinal membranes from patients with traumatic PVR RDs [63].…”
Section: Novel Targets For Proliferative Vitreoretinopathy Inhibitionmentioning
confidence: 99%
“…Kórélettani szempontból citokinek, kemokinek és növekedési faktorok komplex együtthatása alakítja ki a kórfolyamatot (4. ábra, 3. táblázat). A molekulák részletes leírása meghaladná jelen közlemény kereteit, a 4. ábrán igyekeztünk kiemelni a legfontosabb patomechanizmusokat (4,5). Részletes elemzés olvasható többek között Chaudhary közleményében (10).…”
Section: Kórélettanunclassified